Atomic Layer Deposition of Space‐Efficient SnO2 Underlayers for BiVO4 Host–Guest Architectures for Photoassisted Water Splitting. Issue 9 (2nd May 2019) - Lamm, Benjamin; Zhou, Lite; Rao, Pratap; Stefik, Morgan
Abstract: Invited for this month′s cover are the Stefik and Rao groups at the University of South Carolina and Worcester Polytechnic Institute. The image shows a fantastical submarine solar‐water‐splitting process using the host‐guest architectures described in the report. The Full Paper itself is available at 10.1002/cssc.201802566 . Abstract : "To mitigate blocking of pore volume by the interlayer, a very thin SnO2 …" This and more about the story behind the research that inspired the Cover image is presented in the Cover Profile. Read the full text of the corresponding research at10.1002/cssc.201802566 . View the Front Cover here:10.1002/cssc.201901062 .